(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The problems of gender linguistics are the most attractive ones in the modern language study. This is an obviously new branch of science which studies out the focus on difference of means of language between men and women. And not only language but behavior itself. The article constituted a response to male-centered cognitive studies, which had taken modes of thinking associated with dominant men as the norm and appraised the cognitive processes of females. The aim of the research is to study out gender peculiarities in usage the language by two genders (phonology, grammar, morphology, syntax), and the difference between men’s and women’s way of speaking, writing, behavior, etc.